Corrigendum to “Emerging dryland flooding” [Earth-Science Reviews 281 (2026) 105612] - Yuanyuan Bai; Ting Zhang; Stephen E. Darby; Bruno Merz; Albert J. Kettner; Katerina Michaelides; Shijie Jiang; Shuyue Mao; Yiyi Li; Mingfu Guan; Seifu Tilahun; Dongfeng Li (Earth-Science Reviews, 2026)

Emerging dryland flooding - Yuanyuan Bai; Ting Zhang; Stephen E. Darby; Bruno Merz; Albert J. Kettner; Katerina Michaelides; Shijie Jiang; Shuyue Mao; Yiyi Li; Mingfu Guan; Seifu Tilahun; Dongfeng Li (Earth-Science Reviews, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Panta Rhei: a decade of progress in research on change in hydrology and society - Heidi Kreibich; Murugesu Sivapalan; Amir AghaKouchak; Nans Addor; Hafzullah Aksoy; Berit Arheimer; Karsten Arnbjerg-Nielsen; Cynthia Vail-Castro; Christophe Cudennec; Mariana Madruga de Brito; Giuliano Di Baldassarre; David C. Finger; et al. (Hydrological Sciences Journal, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Conflict Dynamics of Post-Retrieval Extinction: A Comparative Analysis of Unconditional and Conditional Reminders Using Skin Conductance Responses and EEG - Dong-ni Pan; Delhii Hoid; Oliver T. Wolf; Christian J. Merz; Xuebing Li (Brain Topography, 2024)

Do oral contraceptives modulate the effects of stress induction on one-session exposure efficacy and generalization in women? - Friederike Raeder; Christian J. Merz; Martin Tegenthoff; Ekrem Dere; Oliver T. Wolf; Jürgen Margraf; Silvia Schneider; Armin Zlomuzica (Psychopharmacology, 2023)
Rationale The administration of glucocorticoids (GC) as an adjunct to exposure represents a promising strategy to improve one-session exposure outcome in anxiety disorders. It remains to be determined whether similar effects can be induced with the use of acute stress. Furthermore, the possible modulation of exposure effects by hormonal factors (e.g., use of oral contraceptives (OCs)) was not explored so far. Objectives We investigated whether acute stress prior to one-session exposure for spider fear affects its efficacy in women using oral contraceptives ( OC ) relative to free-cycling ( FC ) women. In addition, effects of stress on generalization of exposure therapy effects towards untreated stimuli were examined. Methods Women with fears of spiders and cockroaches were randomly assigned to a Stress (n = 24) or No-Stress (n = 24) condition prior to one-session exposure. Of these 48 participants, 19 women used OC (n = 9 in the Stress, and n = 10 in the No-Stress group). All FC women had a regular menstrual cycle and were tested only in the follicular phase of their menstrual cycle. Pre-exposure stress induction was realized with the socially evaluated cold-pressor test. Exposure-induced changes towards treated and untreated fear stimuli were tested with behavioral approach tests for spiders and cockroaches and subjective fear and self-report measures. Results Acute stress did not influence exposure-induced reduction in fear and avoidance of the treated stimuli (spiders). Similarly, stress had no effect on the generalization of exposure-therapy effects towards untreated stimuli (cockroaches). Exposure-induced reduction in subjective fear and self-report measures for treated stimuli was less evident in women using OC specifically after pre-exposure stress. Women using OC had higher levels of subjective fear and scored higher in self-report measures at post-treatment (24 h after exposure) and follow-up (4 weeks after exposure). Conclusions OC intake may represent an important confounding factor in augmentation studies using stress or GC.

Marker-assisted selection in a Pacific oyster population for an antiviral QTL conferring increased survival to OsHV-1 mortality events in Tomales Bay - Konstantin Divilov; Noah Merz; Blaine Schoolfield; Timothy J. Green; Chris Langdon (Aquaculture, 2023)

The influence of tDCS on perceived bouncing/streaming - Maximilian A. Friehs; Marlena J. Stegemann; Simon Merz; Christoph Geißler; Hauke S. Meyerhoff; Christian Frings (Experimental Brain Research, 2023)
Processing ambiguous situations is a constant challenge in everyday life and sensory input from different modalities needs to be integrated to form a coherent mental representation on the environment. The bouncing/streaming illusion can be studied to provide insights into the ambiguous perception and processing of multi-modal environments. In short, the likelihood of reporting bouncing rather than streaming impressions increases when a sound coincides with the moment of overlap between two moving disks. Neuroimaging studies revealed that the right posterior parietal cortex is crucial in cross-modal integration and is active during the bouncing/streaming illusion. Consequently, in the present study, we used transcranial direct current stimulation to stimulate this brain area. In the active stimulation conditions, a 9 cm 2 electrode was positioned over the P4-EEG position and the 35 cm 2 reference positioned over the left upper arm. The stimulation lasted 15 min. Each participant did the bouncing/streaming task three times: before, during and after anodal or sham stimulation. In a sample of N = 60 healthy, young adults, we found no influence of anodal tDCS. Bayesian analysis showed strong evidence against tDCS effects. There are two possible explanations for the finding that anodal tDCS over perceptual areas did not modulate multimodal integration. First, upregulation of multimodal integration is not possible using tDCS over the PPC as the integration process already functions at maximum capacity. Second, prefrontal decision-making areas may have overruled any modulated input from the PPC as it may not have matched their decision-making criterion and compensated for the modulation.

Emergence of heavy tails in streamflow distributions: the role of spatial rainfall variability - H.-J. Wang; R. Merz; S. Yang; L. Tarasova; S. Basso (Advances in Water Resources, 2023)

Pro- and anti-inflammatory macrophages express a sub-type specific purinergic receptor profile - J. Merz; A. Nettesheim; S. von Garlen; P. Albrecht; B. S. Saller; J. Engelmann; L. Hertle; I. Schäfer; D. Dimanski; S. König; L. Karnbrock; K. Bulatova; et al. (Purinergic Signalling, 2021)
Extracellular nucleotides act as danger signals that orchestrate inflammation by purinergic receptor activation. The expression pattern of different purinergic receptors may correlate with a pro- or anti-inflammatory phenotype. Macrophages function as pro-inflammatory M1 macrophages (M1) or anti-inflammatory M2 macrophages (M2). The present study found that murine bone marrow-derived macrophages express a unique purinergic receptor profile during in vitro polarization. As assessed by real-time polymerase chain reaction (PCR), Gαs-coupled P1 receptors A2A and A2B are upregulated in M1 and M2 compared to M0, but A2A 15 times higher in M1. The ionotropic P2 receptor P2X 5 is selectively upregulated in M1- and M2-polarized macrophages. P2X 7 is temporarily expressed in M1 macrophages. Metabotropic P2Y receptors showed a distinct expression profile in M1 and M2-polarized macrophages: Gαq coupled P2Y 1 and P2Y 6 are exclusively upregulated in M2, whereas Gαi P2Y 13 and P2Y 14 are overexpressed in M1. This consequently leads to functional differences between M1 and M2 in response to adenosine di-phosphate stimulation (ADP): In contrast to M1, M2 showed increased cytoplasmatic calcium after ADP stimulation. In the present study we show that bone marrow-derived macrophages express a unique repertoire of purinergic receptors. We show for the first time that the repertoire of purinergic receptors is highly flexible and quickly adapts upon pro- and anti-inflammatory macrophage differentiation with functional consequences to nucleotide stimulation.

Nitrate respiration and diel migration patterns of diatoms are linked in sediments underneath a microbial mat - Elisa Merz; Gregory J. Dick; Dirk de Beer; Sharon Grim; Thomas Hübener; Sten Littmann; Kirk Olsen; Dack Stuart; Gaute Lavik; Hannah K. Marchant; Judith M. Klatt (Environmental Microbiology, 2021)
Summary Diatoms are among the few eukaryotes known to store nitrate (NO 3 − ) and to use it as an electron acceptor for respiration in the absence of light and O 2 . Using microscopy and 15 N stable isotope incubations, we studied the relationship between dissimilatory nitrate/nitrite reduction to ammonium (DNRA) and diel vertical migration of diatoms in phototrophic microbial mats and the underlying sediment of a sinkhole in Lake Huron (USA). We found that the diatoms rapidly accumulated NO 3 − at the mat‐water interface in the afternoon and 40% of the population migrated deep into the sediment, where they were exposed to dark and anoxic conditions for ~75% of the day. The vertical distribution of DNRA rates and diatom abundance maxima coincided, suggesting that DNRA was the main energy generating metabolism of the diatom population. We conclude that the illuminated redox‐dynamic ecosystem selects for migratory diatoms that can store nitrate for respiration in the absence of light. A major implication of this study is that the dominance of DNRA over denitrification is not explained by kinetics or thermodynamics. Rather, the dynamic conditions select for migratory diatoms that perform DNRA and can outcompete sessile denitrifiers.

Unnatural selection of salmon life histories in a modified riverscape - Anna M. Sturrock; Stephanie M. Carlson; John D. Wikert; Tim Heyne; Sébastien Nusslé; Joseph E. Merz; Hugh J. W. Sturrock; Rachel C. Johnson (Global Change Biology, 2020)
Altered river flows and fragmented habitats often simplify riverine communities and favor non‐native fishes, but their influence on life‐history expression and survival is less clear. Here, we quantified the expression and ultimate success of diverse salmon emigration behaviors in an anthropogenically altered California river system. We analyzed two decades of Chinook salmon monitoring data to explore the influence of regulated flows on juvenile emigration phenology, abundance, and recruitment. We then followed seven cohorts into adulthood using otolith (ear stone) chemical archives to identify patterns in time‐ and size‐selective mortality along the migratory corridor. Suppressed winter flow cues were associated with delayed emigration timing, particularly in warm, dry years, which was also when selection against late migrants was the most extreme. Lower, less variable flows were also associated with reduced juvenile and adult production, highlighting the importance of streamflow for cohort success in these southernmost populations. While most juveniles emigrated from the natal stream as fry or smolts, the survivors were dominated by the rare few that left at intermediate sizes and times, coinciding with managed flows released before extreme summer temperatures. The consistent selection against early (small) and late (large) migrants counters prevailing ecological theory that predicts different traits to be favored under varying environmental conditions. Yet, even with this weakened portfolio, maintaining a broad distribution in migration traits still increased adult production and reduced variance. In years exhibiting large fry pulses, even marginal increases in their survival would have significantly boosted recruitment. However, management actions favoring any single phenotype could have negative evolutionary and demographic consequences, potentially reducing adaptability and population stability. To recover fish populations and support viable fisheries in a warming and increasingly unpredictable climate, coordinating flow and habitat management within and among watersheds will be critical to balance trait optimization versus diversification.

A continuous modelling approach for design flood estimation on sub-daily time scale - B. Winter; K. Schneeberger; N.V. Dung; M. Huttenlau; S. Achleitner; J. Stötter; B. Merz; S. Vorogushyn (Hydrological Sciences Journal, 2019)

Cortisol effects on fear memory reconsolidation in women - Shira Meir Drexler; Christian J. Merz; Tanja C. Hamacher-Dang; Oliver T. Wolf (Psychopharmacology, 2016)

Hydrology under change: an evaluation protocol to investigate how hydrological models deal with changing catchments - G. Thirel; V. Andréassian; C. Perrin; J.-N. Audouy; L. Berthet; P. Edwards; N. Folton; C. Furusho; A. Kuentz; J. Lerat; G. Lindström; E. Martin; et al. (Hydrological Sciences Journal, 2015)

Time-varying signal analysis to detect high-altitude periodic breathing in climbers ascending to extreme altitude - A. Garde; B. F. Giraldo; R. Jané; T. D. Latshang; A. J. Turk; T. Hess; M. M. Bosch; D. Barthelmes; T. M. Merz; J. Pichler Hefti; O. D. Schoch; K. E. Bloch (Medical & Biological Engineering & Computing, 2015)

Flood risk assessments at different spatial scales - H. de Moel; B. Jongman; H. Kreibich; B. Merz; E. Penning-Rowsell; P. J. Ward (Mitigation and Adaptation Strategies for Global Change, 2015)

Dependence between flood peaks and volumes: a case study on climate and hydrological controls - L. Gaál; J. Szolgay; S. Kohnová; K. Hlavčová; J. Parajka; A. Viglione; R. Merz; G. Blöschl (Hydrological Sciences Journal, 2015)

Cognitive performance in high-altitude climbers: a comparative study of saccadic eye movements and neuropsychological tests - Tobias M. Merz; Martina M. Bosch; Daniel Barthelmes; Jacqueline Pichler; Urs Hefti; Kai-Uwe Schmitt; Konrad E. Bloch; Otto D. Schoch; Thomas Hess; Alexander J. Turk; Urs Schwarz (European Journal of Applied Physiology, 2013)

Inhibition of quantitative PCR analysis of fungal conidia associated with indoor air particulate matter - James J. McDevitt; Peter S. J. Lees; William G. Merz; Kellogg J. Schwab (Aerobiologia, 2007)

Comparative Risk Assessments for the City of Cologne – Storms, Floods, Earthquakes - G. Grünthal; A. H. Thieken; J. Schwarz; K. S. Radtke; A. Smolka; B. Merz (Natural Hazards, 2006)

Movement of Sacramento Sucker, Catostomus occidentalis, and Hitch, Lavinia exilicauda, during a Spring Release of Water from Camanche Dam in the Mokelumne River, California - Carson A. Jeffres; A. Peter Klimley; Joseph E. Merz; Joseph J. Cech (Environmental Biology of Fishes, 2006)

Variation for neutral markers is correlated with variation for quantitative traits in the plant pathogenic fungus Mycosphaerella graminicola - J. ZHAN; C. C. LINDE; T. JÜRGENS; U. MERZ; F. STEINEBRUNNER; B. A. McDONALD (Molecular Ecology, 2005)
We compared genetic variation and population differentiation at RFLP marker loci with seven quantitative characters including fungicide resistance, temperature sensitivity, pycnidial size, pycnidial density, colony size, percentage of leaves covered by pycnidia (PLACP) and percentage of leaves covered by lesions (PLACL) in Mycosphaerella graminicola populations sampled from four regions. Wide variation in population differentiation was found across the quantitative traits assayed. Fungicide resistance, temperature sensitivity, and PLACP displayed a significantly higher Q ST than G ST , consistent with selection for local adaptation, while pycnidial size, pycnidial density and colony size displayed a lower or significantly lower Q ST than G ST , consistent with constraining selection. There was not a statistical difference between Q ST and G ST in PLACL. We also found a positive and significant correlation between genetic variation in molecular marker loci and quantitative traits at the multitrait scale, suggesting that estimates of overall genetic variation for quantitative traits in M. graminicola could be derived from analysis of the molecular genetic markers.

Improved immunological detection of Spongospora subterranea - U. Merz; J. A. Walsh; K. Bouchek-Mechiche; Th. Oberhänsli; W. Bitterlin (European Journal of Plant Pathology, 2005)

Development of a method to detect and quantify Aspergillus fumigatus conidia by quantitative PCR for environmental air samples - James J. Mcdevitt; Peter S. J. Lees; William G. Merz; Kellogg J. Schwab (Mycopathologia, 2004)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)